Insulin-Related Lipohypertrophy: Lipogenic Action or Tissue Trauma? - Barola, Anjana; Tiwari, Pramil; Bhansali, Anil; Grover, Sandeep; Dayal, Devi (Frontiers in Endocrinology, 2018)
Lipohypertrophy has been suggested as an outcome of lipogenic action of insulin and/or injection-related tissue trauma. In a cross-sectional study, we evaluated the predictors of lipohypertrophy in 372 type 1 diabetes patients (mean age 17.1 years) receiving subcutaneous insulin with pen and/or syringes for ≥3 months. On examining injection sites with inspection and palpation technique, 62.1% patients demonstrated lipohypertrophy. Univariate analysis showed that gender, BMI, HbA1c, injection device, rotation, injection area, needle length, insulin regimen, and total daily dose of insulin were associated with lipohypertrophy (p < 0.05). Notably, the mean needle reuse was comparable in patients with or without lipohypertrophy (8.1 vs. 7.2, p = 0.534). In multivariate logistic regression, gender, HbA1c, TDD, injection devices, and needle length lost its significance. Further, injections over smaller area (≤8.5 × 5.5 cm) and non-rotation of sites were found to be strongest independent predictor of lipohypertrophy (p < 0.0005 for both) with increased odds of 23.2 (95% CI 9.1–59.2) and 6.3 (95% CI 3.4–11.9) times, respectively. Being underweight was also a significant independent predictor (odds ratio [OR] 13.0 [95% CI 2.2–75.2], p = 0.004). Compared to rapid plus long-acting analogs, regular insulin plus long-acting analogs and conventional premixed insulin users had 3.2 (95% CI 1.5–6.8, p = 0.003) and 4.6 (95% CI 1.4–15.7, p = 0.014) fold higher risk of lipohypertrophy (mean injection frequency 4.01 vs. 4.01 vs. 2.09, respectively). Sub-group analysis showed that lipohypertrophy was 79% less likely in patients with multiple daily injections (≥4) than twice-daily regimen (OR 0.21, p < 0.0005). Moreover, lipohypertrophy was reduced to half with bolus doses of rapid-acting insulin analogs than regular insulin (p = 0.003), even though mean injection frequency was comparable (4.01 vs. 3.93, p = 0.229). This difference was statistically insignificant for basal doses with NPH or long-acting analogs (p = 0.069). Therefore, injection area, rotation, BMI, and insulin regimen are the best predictors of lipohypertrophy and together could correctly identify lipohypertrophy status in 84.4% patients with excellent discrimination capability (AUC = 0.906, p < 0.0005). In conclusion, findings of our study suggest that delivering rapidly absorbed insulin analogs over large injection area along with greater split of total daily doses reduce insulin-induced lipogenesis and outplay tissue trauma added through frequent injections and needle reuse.